A Nicer View on the 2020 Magnetar-Like Outburst of Psr J1846−0258 - Espinoza-Romo, C (Institute of Physics, 2023)
We report on our monitoring of the strong-field magnetar-like pulsar PSR J1846−0258 with the Neutron Star Interior Composition Explorer (NICER) and the timing and spectral evolution during its outburst in 2020 August. Phase-coherent timing solutions were maintained from 2017 March through 2021 November, including a coherent solution throughout the outburst. We detected a large spin-up glitch of magnitude Δν/ν = 3 × 10−6 at the start of the outburst and observed an increase in pulsed flux that reached a factor of more than 10 times the quiescent level, a behavior similar to that of the 2006 outburst. Our monitoring observations in 2020 June and July indicate that the flux was rising prior to the Swift announcement of the outburst on 2020 August 1. We also observed several sharp rises in the pulsed flux following the outburst and the flux reached quiescent level by 2020 November. The pulse profile was observed to change shape during the outburst, returning to the preoutburst shape by 2021. Spectral analysis of the pulsed emission of NICER data shows that the flux increases result entirely from a new blackbody component that gradually fades away while the power law remains nearly constant at its quiescent level throughout the outburst. Joint spectral analysis of NICER and simultaneous NuSTAR data confirms this picture. We discuss the interpretation of the magnetar-like outburst and origin of the transient thermal component in the context of both a pulsar-like and a magnetar-like model. © 2023. The Author(s). Published by the American Astronomical Society.